2017
DOI: 10.1182/bloodadvances.2017009423
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance induction by nonmyeloablative haploidentical HSCT combining T-cell depletion and posttransplant cyclophosphamide

Abstract: Key Points• This study lays the foundation for the use of nonmyeloablative GVHD-free haploidentical HSCT.• This approach offers treatment of hematological diseases and a safe potential platform for cell therapy and organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Clearly, there are two distinct barriers to these unique transplants. On one hand, rejection by the host must be overcome, which can be achieved in mice according to our protocol using 2 Gy TBI, plus post-transplantation Cy, and by 3 Gy TBI plus Cy in humans (Aversa et al, 2017). However, to make space in the lung niche so as to overcome stem cell competition with endogenous lung progenitors, irrespective of the immune rejection barrier, we need, as explained above, to combine NA with subsequent 6 Gy TBI 2 days later.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Clearly, there are two distinct barriers to these unique transplants. On one hand, rejection by the host must be overcome, which can be achieved in mice according to our protocol using 2 Gy TBI, plus post-transplantation Cy, and by 3 Gy TBI plus Cy in humans (Aversa et al, 2017). However, to make space in the lung niche so as to overcome stem cell competition with endogenous lung progenitors, irrespective of the immune rejection barrier, we need, as explained above, to combine NA with subsequent 6 Gy TBI 2 days later.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol used was based on our recent work in haploidentical HSC transplantation (HSCT), which showed that a combination of T cell-depleted ''megadose'' HSCT with Cy administration following allogeneic BMT leads to marked chimerism upon treatment with a relatively safe non-myeloablative conditioning (Aversa et al, 2017). This approach was based on early studies by the John Hopkins group (Luznik et al, 2012) which showed that Cy is nontoxic to HSCs because of their high expression of the detoxifying enzyme aldehyde dehydrogenase, whereas activated alloreactive T cells are sensitive to deletion by this agent.…”
Section: Induction Of Hematopoietic Chimerism and Immune Tolerance Bymentioning
confidence: 99%
See 3 more Smart Citations